Asymmetric Hydrocyanation of Nitroolefins Catalyzed by an Aluminum(III) Salen Complex. Issue 9 (1st August 2014) - Jakhar, Ajay; Sadhukhan, Arghya; Khan, Noor‐ul H.; Saravanan, S.; Kureshy, Rukhsana I.; Abdi, Sayed H. R.; Bajaj, Hari C.
Abstract Chiral AlIII salen complexes were synthesized and used as catalysts for the asymmetric hydrocyanation of nitroolefins using 4‐phenylpyridine N‐oxide as an additive and trimethylsilyl cyanide (TMSCN) as a source of cyanide. An excellent yield of β‐nitronitrile (87 %) and enantioselectivity (90 %) were achieved if (2‐nitrovinyl)cyclohexane was used as a substrate at −15 °C in 16 h. To understand the interaction of the AlIII salen complex and additive, NMR and IR spectroscopic studies revealed that 4‐phenylpyridine N‐oxide acts both as an axial ligand and helps to activate the cyanide source TMSCN, which thereby increases the reactivity. A catalytic cycle was proposed based on the spectroscopic studies.